Human-centered integration of small wind turbines in urban environments: a semi-systematic review from an industrial design perspective - Bereziartua-Gonzalez, Leire; Retegi, Aiur; Ukar, Olatz (Frontiers in Sustainable Cities, 2025)
The increasing demand for renewable energy solutions, coupled with the urgent need to mitigate climate change, has positioned urban wind energy, particularly small wind turbines (SWTs), as a viable alternative for cities. This study aims to explore the socio-technical challenges and opportunities associated with the integration of SWTs in urban environments, emphasizing the critical role of design in addressing these challenges. Through a semi-systematic review of existing literature, we analyze the various factors influencing the acceptance and effectiveness of SWTs, including urban aesthetics, noise levels, safety concerns, and the democratization of energy technologies. We propose a comprehensive framework that incorporates human perspectives into the design process, advocating for interdisciplinary collaboration among designers, engineers, and social scientists. By engaging citizens as co-creators in the development of SWT solutions, we can better align technological innovations with the needs and values of urban communities. This participatory approach not only enhances the design quality but also fosters trust and acceptance among residents, ultimately contributing to a more sustainable energy transition. The findings of this research provide valuable insights, highlighting the importance of human-centered design in the successful implementation of renewable energy technologies in urban settings. By addressing the complexities of urban wind energy through a holistic lens, this study contributes to the ongoing discourse on sustainable urban development and the role of community engagement in shaping the future of energy solutions.